Interception of an exotic plant parasitic nematode (Rotylenchus minutus) on African potato (Hypoxis hemerocallidea) from Swaziland - KHAN, ZAKAULLAH; MAHAMOOD, M; LAL, ARJUN; AKHTAR, JAMEEL; PARAKH, D B (The Indian Journal of Agricultural Sciences, 2013)
During the quarantine processing at NBPGR, New Delhi Rotylenchus minutus intercepted on corms of African potato, Hypoxis hemerocallidea, which were imported from Swaziland. Here, African potato is reported as a new host record for R. minutus and this species has not been reported in India. Infected corms were given dip treatment in 0.2% formalin solution for 15 min to eliminate nematode infection. Six months later, post entry quarantine inspection was conducted on corms grown in potted soil at NBPGR, New Delhi. All samples were found free from R. minutus. This study highlights the importance of interception of R. minutus on a new host in minimizing risk of introducing exotic nematode into country. Moreover, prophylactic treatment of corms with 0.2% formalin assisted in salvaging the material infected with R. minutes.